Surgical Correction of Congenital Bilateral Patellar Luxation in a Pup - A Case Report - Arif, Mohd; Murthy, KM Srinivasa; Ranganath, L (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Luxation of patella may be congenital or traumatic origin, and can affect any breed. The congenital form is related to developmental abnormalities of the limb that create malalignment of quadriceps group of muscles. With underlying abnormalities of hip and stifle joint congenital lateral patellar luxation have skeletal abnormalities like retroversion of femoral head and neck, coxa vara (altered angle of inclination), genu valgum and shallow trochlear groove with poorly developed trochlear ridges (Denny and Butterworth, 2006). Luxation of patella is a common cause of lameness in dog which can be in medial or lateral displacement. The incidence of medial patellar luxation is 5 times more than lateral luxation and is seen more in large breeds of dogs. Lateral patellar luxation may predispose the dogs to knock knee (genu valgum) and cow hock (hock valgus) condition (Robins, 1990). The cause of lateral patellar luxation is unknown but is thought to be related to anteversion or coxa valga of the coxofemoral joint, which shifts the line of force produced by the pull of quadriceps lateral to the longitudinal axis of the trochlear groove. This abnormally directed lateral force pulls the patella from the trochlear sulcus causing skeletal abnormalities (Fossum, 2002)